3-6(-5y+4)=3(-y+1)-6

Simple and best practice solution for 3-6(-5y+4)=3(-y+1)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3-6(-5y+4)=3(-y+1)-6 equation:


Simplifying
3 + -6(-5y + 4) = 3(-1y + 1) + -6

Reorder the terms:
3 + -6(4 + -5y) = 3(-1y + 1) + -6
3 + (4 * -6 + -5y * -6) = 3(-1y + 1) + -6
3 + (-24 + 30y) = 3(-1y + 1) + -6

Combine like terms: 3 + -24 = -21
-21 + 30y = 3(-1y + 1) + -6

Reorder the terms:
-21 + 30y = 3(1 + -1y) + -6
-21 + 30y = (1 * 3 + -1y * 3) + -6
-21 + 30y = (3 + -3y) + -6

Reorder the terms:
-21 + 30y = 3 + -6 + -3y

Combine like terms: 3 + -6 = -3
-21 + 30y = -3 + -3y

Solving
-21 + 30y = -3 + -3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '3y' to each side of the equation.
-21 + 30y + 3y = -3 + -3y + 3y

Combine like terms: 30y + 3y = 33y
-21 + 33y = -3 + -3y + 3y

Combine like terms: -3y + 3y = 0
-21 + 33y = -3 + 0
-21 + 33y = -3

Add '21' to each side of the equation.
-21 + 21 + 33y = -3 + 21

Combine like terms: -21 + 21 = 0
0 + 33y = -3 + 21
33y = -3 + 21

Combine like terms: -3 + 21 = 18
33y = 18

Divide each side by '33'.
y = 0.5454545455

Simplifying
y = 0.5454545455

See similar equations:

| log^6x=3 | | 3(x-2)+7=3x+27 | | -19(2a-3b+8c)= | | 13x-2(4x-5)=66-3x | | 5z^2-37zy+42y^2=0 | | 72+24w=288 | | 3(4x-3)= | | 2ln(x)=4 | | 24+16p=4p | | 24x-32=24x+36 | | 5+2j=27 | | 50-82d-86-8d+7+4d= | | -5x+(2+x)= | | 5+2j=25 | | 6w^3y^6-3u^3w^2/6w^5 | | y=(2x+5)2 | | 27=5+2j | | q=p-30 | | -4.8(x+3)+6.5(x-1.2)=-25.09 | | 19+n=42 | | -4y+3x=28 | | 15+4n=63 | | 6x*7y= | | (a^-2b/ab^6)^-3 | | -5+9=a+5-7 | | X-53=27 | | 4b=80 | | 0.06=n(7) | | 11a=77 | | 8x+8=4x+2 | | 10-1/3n= | | 5v^2-10v-175=0 |

Equations solver categories